Islamic banking in Indonesia and Malaysia: Comparative insights into sharia compliance, profitability, and governance - Lestary, Dini; Aulia Azimi; Fitri Jayanti; Samsul Hidayat (JIFA (Journal of Islamic Finance and Accounting), 2024)
The growing prominence of Islamic banks in Southeast Asia highlights the importance of understanding their financial performance to maintain public trust and enhance competitiveness. This research aims to compare the financial performance of Islamic commercial banks (BUS) in Indonesia and Malaysia by employing the Sharia Conformity and Profitability (SCnP) method and analyzing the application of the Islamic Corporate Governance (ICG) index. Using a quantitative descriptive approach, the study utilizes financial performance data from the 2021-2022 annual reports of selected banks. The SCnP method categorizes Sharia banks into four quadrants: Upper Right Quadrant (URQ), Lower Right Quadrant (LRQ), Upper Left Quadrant (ULQ), and Lower Left Quadrant (LLQ). Results indicate that Bank BCA Syariah (BCAS), Bank Syariah Indonesia (BSI), and National Pension Savings Bank (BTPNS) demonstrate superior performance, as they are positioned in the URQ. Additionally, the ICG analysis reveals that Bank Muamalat Malaysia Berhad (BMMB) achieves the highest governance index score at 62%, followed by BCAS from Indonesia at 56%. These findings provide valuable insights for policymakers and bank managers, emphasizing the critical role of governance and Sharia compliance in driving the success of Islamic banks in the region